Disposable Plastic Cuvettes for Thrombelastography - Loeliger, E. A; Veltkamp, J. J; Mattern, Mieke J; Hooij, Henriëtte J (Thrombosis and Haemostasis, 1963)
Thrombelastography can be performed by means of disposable plastic cuvettes instead of metallic cuvettes. There is no important difference between the curves obtained in cuvettes of the two different materials. Reproducibility plastic cuvettes appears to be as good as in metallic cuvettes; reproducibility seems to be even better. The use of plastic disposable cuvettes has important practical advantages.